Field notes contributed by Ruth Phipps, Shenandoah, Iowa, winter 1983-1984 - Phipps, Ruth O.et al (1983)
Field notes contributed by Ruth Phipps, Shenandoah, Iowa, winter 1983-1984, included observations from Marie Spears, Betty Walters, Don Priebe and Jeannine Owen. Observations marked as fide were a Greater White-fronted Goose and Cooper's Hawk in Fremont County, a Northern Goshawk in Page County, and a Short-eared Owl north of Shenandoah. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1983-1984. Epson - sheet feed